Cognitive deficits in psychiatric disorders: Current status - Trivedi, J.K. (Medknow Publications, 2006)
Cognition denotes a relatively high level of processing of specific information including thinking, memory, perception, motivation, skilled movements and language. Cognitive psychology has become an important discipline in the research of a number of psychiatric disorders, ranging from severe psychotic illness such as schizophrenia to relatively benign, yet significantly disabling, non-psychotic illnesses such as somatoform disorder. Research in the area of neurocognition has started unlocking various secrets of psychiatric disorders, such as revealing the biological underpinnings, explaining the underlying psychopathology and issues related to course, outcome and treatment strategies. Such research has also attempted to uproot a number of previously held concepts, such as Kraepelin's dichotomy. Although the range of cognitive problems can be diverse, there are several cognitive domains, including executive function, attention and information processing, and working memory, which appear more frequently at risk. A broad range of impairment across and within the psychiatric disorders are highlighted in this oration. The oration summarizes the studies investigating cognitive processing in different psychiatric disorders. I will also discuss the findings of my own research on neurocognitive deficits in mood disorders, schizophrenia, obsessive–compulsive disorder, somatoform disorder, including studies on ‘high-risk’ individuals. Tracing the evaluation of neurocognitive science may provide new insights into the pathophysiology and treatment of psychiatric disorders.